AN ANALYSIS OF ACADEMIC WRITING ACQUISITION OF UNIVERSITY STUDENTS IN INDONESIAN CLASSES - I Nyoman Suwandi (International Journal of Social Science, 2022)
Academic writing is arguably the most important skill in academic contexts and also the most difficult skill for most students to master. Consequently, extra learning efforts are necessary to be carried out by the students to ensure that their acquisition up to the present academic requirement. This study was conducted to find out the acquisition of students’ academic writing skills. Study was conducted in Indonesian classes consisting of 30 students as the sample of the study which were selected by random sampling technique. Valid and reliable research instruments in the form of essay test was administered to the sample to collect the required data. This study found that university students of Indonesian classes have sufficient acquisition in academic writing. Therefore, this study implies that academic writing of the students should continually be improved to ensure that the students have higher acquisition in academic writing.